Symbiont-derived β-1,3-glucanases in a social insect: mutualism beyond nutrition - Rosengaus, Rebeca B.; Schultheis, Kelley F.; Yalonetskaya, Alla; Bulmer, Mark S.; DuComb, William S.; Benson, Ryan W.; Thottam, John P.; Godoy-Carter, Veronica (Frontiers in Microbiology, 2014)
Termites have had a long co-evolutionary history with prokaryotic and eukaryotic gut microbes. Historically, the role of these anaerobic obligate symbionts has been attributed to the nutritional welfare of the host. We provide evidence that protozoa (and/or their associated bacteria) colonizing the hindgut of the dampwood termite Zootermopsis angusticollis, synthesize multiple functional β-1,3-glucanases, enzymes known for breaking down β-1,3-glucans, the main component of fungal cell walls. These enzymes, we propose, may help in both digestion of ingested fungal hyphae and protection against invasion by fungal pathogens. This research points to an additional novel role for the mutualistic hindgut microbial consortia of termites, an association that may extend beyond lignocellulolytic activity and nitrogen fixation to include a reduction in the risks of mycosis at both the individual- and colony-levels while nesting in and feeding on microbial-rich decayed wood.